Global Lake Ecological Observatory Network (Gleon): The Evolution of Grassroots Network Science - Weathers, Kathleen C. (2013)
A grassroots, global network to examine lake function using sensor data? Why not? That was the perspective of Drs. Tim Kratz (limnologist), David Hamilton (limnologist), Peter Arzberger (mathematician), and Fang-Pang Lin (computer scientist) in 2004 when they hatched the idea of the Global Lake Ecological Observatory Network (Fig. 1). Nine years later, with over 380 members from 40 countries, and 50 publications to its credit, GLEON is growing at a rapid pace and pushing the boundaries of the practice of network science. GLEON is really three networks: a network of lakes, data, and people.